Constraining the duration of ram pressure stripping features in the optical from the direction of jellyfish galaxy tails - Salinas, Vicente; Jaffé, Yara L; Smith, Rory; Shinn, Jong-Ho; Crossett, Jacob P; Gullieuszik, Marco; González i Torà, Gemma; Piraino-Cerda, Franco; Poggianti, Bianca; Vulcani, Benedetta; Biviano, Andrea; Lourenço, Ana C C; et al. (Monthly notices of the Royal Astronomical Society, 2024)
Ram pressure stripping is perhaps the most efficient mechanism for removing gas and quenching galaxies in dense environments, as they move through the intergalactic medium. Extreme examples of on-going ram pressure stripping are known as jellyfish galaxies, characterized by a tail of stripped material that can be directly observed in multiple wavelengths. Using the largest homogeneous broad-band optical jellyfish candidate sample in local clusters known to date, we measure the angle between the direction of the tails visible in the galaxies, and the direction towards the host cluster centre. We find that 33 per cent of the galaxy tails point away from the cluster centre, 18 per cent point towards the cluster centre, and 49 per cent point elsewhere. Moreover, we find stronger signatures of ram pressure stripping happening on galaxies with a tail pointing away and towards the cluster centre, and larger velocity dispersion profiles for galaxies with tails pointing away. These results are consistent with a scenario where ram pressure stripping has a stronger effect for galaxies following radial orbits on first infall. The results also suggest that in many cases, radially infalling galaxies are able to retain their tails after pericenter and continue to experience significant on-going ram pressure stripping. We further constrain the lifespan of the optical tails from the moment they first appear to the moment they disappear, by comparing the observed tail directions with matched N-body simulations through Bayesian parameter estimation. We obtain that galaxy tails appear for the first time at [approximately] 1.16R200 and disappear [approximately] 660 Myr after pericenter.
Veröffentlicht: 27. Juli 2024
Gesehen am 10.07.2025